2020
DOI: 10.1038/s41598-020-76259-z
|View full text |Cite
|
Sign up to set email alerts
|

A local difference in blood–brain barrier permeability in the caudate putamen and thalamus of a rat brain induced by focused ultrasound

Abstract: A blood–brain barrier (BBB) opening induced by focused ultrasound (FUS) has been widely studied as an effective way of treating brain diseases. We investigate the effect of ultrasound’s incidence angle at caudate putamen (Cp) and thalamus (Th) of the rat brain by inducing the same power of focused ultrasound that corresponds to the acoustic pressure of 0.65 MPa in free field. The BBB permeability (Ktrans) was quantitatively evaluated with dynamic contrast-enhanced magnetic resonance imaging. The group averaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The acoustic pressure of FUS was used by 0.60 MPa (TH) and 0.65 MPa (CP) for group-0.65 MPa and by 0.75 MPa (TH) and 0.80 MPa (CP) for group-0.80 MPa, respectively. In an earlier study, different degrees of BBBD were found depending on the brain region, resulting in smaller BBB permeability in CP compared to TH ( Huh et al, 2020 ). Thus, by applying different acoustic pressures, the two target areas showed comparable degrees of BBBD, comparable patterns of DTI parameters, and histological results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The acoustic pressure of FUS was used by 0.60 MPa (TH) and 0.65 MPa (CP) for group-0.65 MPa and by 0.75 MPa (TH) and 0.80 MPa (CP) for group-0.80 MPa, respectively. In an earlier study, different degrees of BBBD were found depending on the brain region, resulting in smaller BBB permeability in CP compared to TH ( Huh et al, 2020 ). Thus, by applying different acoustic pressures, the two target areas showed comparable degrees of BBBD, comparable patterns of DTI parameters, and histological results.…”
Section: Discussionmentioning
confidence: 97%
“…Two sonication groups and a sham-controlled group were determined using MR signal analysis. Based on earlier studies, different degrees of BBBD were found depending on the brain region, resulting in smaller BBB permeability in CP compared to TH ( Huh et al, 2020 ); thus, we experimentally determined how to apply a higher acoustic power to CP than to TH, such that the target regions showed comparable degrees of BBBD. We designated the sonication groups as group-0.65 MPa and group-0.80 MPa, which indicated the corresponding acoustic power applied to CP.…”
Section: Methodsmentioning
confidence: 99%
“…BBBD depends on various factors, such as the microbubble dose and sonication angle [ 7 , 28 ]. The selection of optimal ultrasound parameters is critical for safe BBBD as it determines the acoustic cavitation level by microbubble activity [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…This effect can last for as long as 7 weeks (Table 3). 25,28,49,105,111 For some cases, astrocyte reactivity was reported to recover within 2 weeks for single location treatment and within 13 weeks for large volume treatment. 25,111 In a high-grade murine glioma model, moderate and heterogeneous astrocyte activity (GFAP expression) was observed in tumor regions without FUS+MB treatment, whereas increased astrogliosis and astrocyte activity were observed in regions of tumors targeted with FUS.…”
Section: Effects Of Fus+mb On Astrocytesmentioning
confidence: 99%
“…Several preclinical studies have observed FUS+MB-induced microglia activation using methods from immunohistochemistry staining of Iba1 to noninvasive PET imaging with [18F]-DPA714, a biomarker of translocator protein (TSPO) at the site of BBB disruption. 25,28,49,53,111,121 FUS+MB-induced microglia activation occurred as early as 1 hour after sonication and may last for as long as 7 weeks while the recovery time ranges from 24 hours to 13 weeks (Table 4). Both single and multiple treatments of FUS+MB have been shown to activate microglia in the sonicated cortex.…”
Section: Effects Of Fus+mb On Microgliamentioning
confidence: 99%